Mouthguard sensor measures lactate to improve performance of athletes - Ford, J. (The Engineer, 2018)
A mouthguard is being developed to continuously monitor lactate, glucose or other analytes, an advance that could help athletes optimise their performances. mouthguard Modified mouthguard monitors levels of lactate (Credit: NextFlex)